THE EFFECT OF SOCIAL MEDIA USE ON EMPLOYEE PERFORMANCE WITH TALENT MANAGEMENT AS A MODERATING VARIABLE - Kardini, Ni Luh; Utami, Eva Yuniarti; Hendratmoko, Suseno; Yakin, Ikram; Inzani SL, J Fuji (ITB AAS Indonesia Surakarta, 2024)
Abstract This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as the most fundamental benchmark for building arguments, novelty and research gaps in the research being carried out. The data used in this research is primary data that researchers collected by distributing online questionnaires to Astra employees spread throughout Indonesia. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this research show shows that the Social Media variable has a positive relationship and a significant influence on employee performance. This is because the P-Values value is positive and is below the significance level of 0.05, namely 0.004. This result is because the better employees are at using social media, the easier it will be for employees to complete work, such as if they don't know how to do something, they can search on YouTube, Google and other platforms, and can ask someone who knows better. Apart from that, social media can make it easier to communicate without meeting in person, simplify difficult administration, and so on which can make it easier for employees to complete their work so that they can improve employee performance. Apart from that, in the second row of the table, the three path coefficients show the same results if the Talent Management variable can moderate the influence of the Social Media variable on Employee Performance because of the same thing, namely the P-Values value which is positive and is below the significance level of 0.05, namely 0.000, which is more significant. from direct testing 0.004. Thus, the first and second hypotheses in this research can be accepted and proven. Keywords: Social Media, Talent Management, Employee Performance